The Sosialisasi Good Manufacturing Practice Kepada UMKM Kuliner Kelurahan Karang Rejo - Lina Yuliana; Gerry Rayhard Tangkilisan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, both in terms of the number of businesses and job creation. However, due to the lack of awareness of MSME actors of state standardization in the form of procedures established in a food management. The socialization of Good Manufacturing Practice (GMP) aims to increase the awareness of MSME actors of state standardization in the form of procedures applied in culinary management, with the hope of producing food and beverage products that are of much higher quality and can increase business profits. Good manufacturing practice (GMP) is a way of management and work methods that are in accordance with standards for producing food and beverages that are safe, quality and suitable for consumption. This socialization activity is divided into several stages, namely; location survey, literature study, making activity materials, preparation and implementation, evaluation. The targets of this activity are culinary MSME players in Karang Rejo Village, by first analyzing the problems faced by MSME players. Based on the results of this activity, MSME business owners will understand the importance of processing quality food products and be able to apply Good Manufacturing Practice (GMP) in processing and producing quality and safe products for consumers so that in terms of packaging and sanitary hygiene so as to increase sales profits.